1982
DOI: 10.1007/bf00428151
|View full text |Cite
|
Sign up to set email alerts
|

Heroin and cocaine intravenous self-administration in rats: Mediation by separate neural systems

Abstract: The hypothesis that separate neural systems mediate the reinforcing properties of opiate and psychomotor stimulant drugs was tested in rats trained to lever-press of IV injections of either cocaine or heroin during daily 3-h sessions. Pretreatment with the opiate receptor antagonist drug naltrexone produced dose-dependent increases in heroin self-administration, but had no effect on the rate or pattern of cocaine self-administration. Similarly, pretreatment with low doses of the dopamine antagonist drug alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
255
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 537 publications
(284 citation statements)
references
References 32 publications
26
255
3
Order By: Relevance
“…SA. This observation, consistent with previous studies on the effect of DA receptor antagonists on the acquisition of heroin SA (Ettenberg et al, 1982), excludes the possibility that impairment of cocaine SA induced by silencing of NAc shell DA D1aR is due to a general impairment of instrumental learning or motivation. Collectively therefore, the impairment of cocaine self-administration, elicited by silencing of D1aR expression in the NAc shell, can be interpreted as due to a devaluation of the reinforcing properties of cocaine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…SA. This observation, consistent with previous studies on the effect of DA receptor antagonists on the acquisition of heroin SA (Ettenberg et al, 1982), excludes the possibility that impairment of cocaine SA induced by silencing of NAc shell DA D1aR is due to a general impairment of instrumental learning or motivation. Collectively therefore, the impairment of cocaine self-administration, elicited by silencing of D1aR expression in the NAc shell, can be interpreted as due to a devaluation of the reinforcing properties of cocaine.…”
Section: Discussionsupporting
confidence: 91%
“…At low doses it selectively increases responding for cocaine without affecting responding for heroin, while at higher doses, it reduces responding for both drugs (Ettenberg et al, 1982). These observations have been interpreted to mean that low doses of flupentixol selectively impair cocaine reinforcement, while higher doses exert a general effect on motivation and on its expression into action (Ettenberg et al, 1982). Given these premises, manipulation of DA D1aR expression by RNAi in the NAc shell versus core was utilized to investigate the role of DA in these two NAc subdivisions in cocaine reinforcement.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, the monoamine releaser damphetamine was tested as a candidate 'agonist' medication, because it produces many cocaine-like effects (Colpaert et al, 1979;Hoffman, 2001), and because several recent clinical studies reported promising results with d-amphetamine maintenance in the treatment of stimulant abuse (Fleming and Roberts, 1994;Charnaud and Griffiths, 1998;White, 2000;Grabowski et al, 2001). Flupenthixol was tested as a representative 'antagonist' medication, because it is a nonselective antagonist at D1 and D2 dopamine receptors that was reported to block some abuse-related effects of cocaine (Ettenberg et al, 1982;Baker et al, 1993) and that has also been evaluated as a treatment for cocaine dependence (Soyka and DeVry, 2000;Evans et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine is a psychostimulant that is addictive and readily self-administered by humans and various animal species (Ettenberg et al 1982;Koob 1992;Ritz et al 1988). Cocaine decreases dopamine reuptake by inhibiting the dopamine transporter in the mesolimbic system, an effect thought to be critical for self-administration and other behaviors associated with cocaine reinforcement (Goeders and Smith 1983;Karler et al 1989;Ritz et al 1987;RoddHenricks et al 2002).…”
Section: Introductionmentioning
confidence: 99%